Ownership Structure on Tax Avoidance with Independent Commissioner as Moderation - Sudirman Sudirman; Almatius Setya Marsudi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study was conducted to examine the effect of ownership structure on tax avoidance, with independent commissioners as a moderating variable. The research objects are mining companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The analytical technique used is Multiple Linear Regression. The test results show that institutional ownership has a positive effect on tax avoidance, while family ownership and managerial ownership do not affect tax avoidance. Additionally, the proportion of independent commissioners cannot moderate institutional, family, or managerial ownership concerning tax avoidance.